A bi-objective robust model for berth allocation scheduling under uncertainty. (October 2017) - Xiang, Xi; Liu, Changchun; Miao, Lixin
Highlights: Study the berth allocation problem with the consideration of uncertainty factors. A bi-objective robust berth allocation model, which focuses on economic performance and customer satisfaction, is formulated. An adaptive grey wolf optimizer algorithm is developed. Computational experiments are conducted to verify the effectiveness of the algorithm and model. Abstract: This study examines the berth allocation problem with the consideration of uncertainty factors, including the arrival and operation times of the calling vessels. A bi-objective robust berth allocation model, which focuses on economic performance and customer satisfaction, is formulated. The model aims to optimize the robustness of the berth allocation policy, and an adaptive grey wolf optimizer algorithm is developed to solve the proposed model. The performance of the heuristic is evaluated through randomly generated instances. Experimental results show that the proposed heuristic provides good solution quality and calculation efficiency.